A checklist of orchids of Biligiri Rangaswamy Temple Tiger Reserve, Western Ghats, India - Jayanthi, J. (Universidad de Costa Rica, 2023)
This paper provides a comprehensive account of the orchid diversity in the Biligiri Rangaswamy Temple Tiger Reserve (BRTTR), Karnataka, India. A total of 97 orchid species belonging to 33 genera were documented. This includes 50 terrestrial and 47 epiphytic orchids, including one mycoheterotrophic orchid, Epipogium roseum, and a climbing leafless Vanilla walkerae. Additionally, 39 endemic orchids were documented during the study. The evergreen forests provide the most habitable conditions for the orchids in BRTTR. The present study adds 26 species to the orchid flora of BRTTR. About 49% of the orchid flora of Karnataka state and 32% of orchids of Western Ghats is found in BRTTR, making this area a microcenter for orchid diversity.